Military intervention, stabilisation and peace the search for stability - Dennys, Christian (Cass military studies, 2014)
This book examines international military interventions that have supported stability in four communities in Afghanistan and Nepal, in an attempt to analyse their success and improve this in future. This is the first in-depth village-level assessment of how local populations conceive of stability and stabilisation, and provides a theory and model for how stability can be created in communities during and after conflict. The data was collected during field research from 2010-12. In Afghanistan the conflicts examined include the invasion of the Soviet Union in 1979, the civil war from 1992 and the rise and fall of the Taliban. In Nepal the research examined the origins of the Maoist movement and the start of the People's War in 1996 to its completion in 2006 and the subsequent Madeshi Andolan in 2007. The book argues that international, particularly Western, notions of stability and stabilisation processes have failed to grasp the importance of local political legitimacy formation, which is a vital aspect of contemporary statebuilding of a 'non-Westphalian' nature. The interventions, across defence, diplomatic and defence lines, have also at times undermined one another and in some cases contributed to instability. The work argues that the theories that structure interventions to address threats to international stability in 'fragile' states are insufficient to explain or achieve the goal of stability. This book will be of interest to students of stabilisation operations, statebuilding, peacebuilding, counterinsurgency, war and conflict studies and security studies in general.